Perspectivas no design sustentável: uma análise comparativa entre telhas convencionais e telhas de concreto com resíduo de bauxita - GOMES, Mayara Maluf (2022)
Towards a more sustainable society that aims to consciously minimize environmental impacts, sustainable design combined with social innovation becomes an indispensable agent for the development of this process, fostering new perspectives through the study of materials and residues, encouraging scientific research and the training of professionals who are dedicated to finding practical and viable solutions for different needs. Rethinking production processes, the life cycles of materials and products, recycling, reuse of waste, development of new artifacts among other possibilities are increasingly constant practices inside and outside Universities. According to the International Council for Research and Innovation (CIB), civil construction is the sector that consumes the most natural resources as well as the one that most uses energy in an ostensible way. It is possible to reduce the damage generated by civil construction through the development of sustainable products, for example as the concrete tile with bauxite residue which was the study case analyzed in this dissertation. This research aims to develop a comparative analysis between conventional tiles and concrete tile with bauxite residue, seeking the feasibility for future application in social and affordable housing in the city of São Luís, MA. The literature review contains the theoretical basis necessary for a greater understanding of the perspectives in sustainable design, looking for authors who approach sustainability in design and social innovation, discussing possible paths for a more sustainable society as well as delving into the ceramics and concrete tiles and their respective Technical Norms, the bauxite residue and its applications in the civil construction sector. The second stage addressed the analyzes to be carried out in the laboratory for concrete tiles with 30% replacement of sand by bauxite residue, explaining the materials and methods used. The third and final stage consisted of understanding the results found and developing the comparative analysis, a specific objective proposed in this dissertation. It was concluded that the concrete tiles with partial replacement of 30% of the sand by the bauxite residue achieved satisfactory and predicted results within the NBR 13858-2, thus encouraging the continuity of more specific and in-depth tests, so that in the future it may be possible their large-scale production for application in affordable and social housing in São Luís, MA. Keywords: